2020
DOI: 10.1007/s11906-020-01067-9
|View full text |Cite
|
Sign up to set email alerts
|

ENaC in Salt-Sensitive Hypertension: Kidney and Beyond

Abstract: Purpose of Review The main goal of this article is to discuss the role of the epithelial sodium channel (ENaC) in extracellular fluid and blood pressure regulation. Recent Findings Besides its role in sodium handling in the kidney, recent studies have found that ENaC expressed in other cells including immune cells can influence blood pressure via extra-renal mechanisms. Dendritic cells (DCs) are activated and contribute to salt-sensitive hypertension in an ENaC-dependent manner. We discuss recent studies on ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 147 publications
1
54
0
Order By: Relevance
“…Recently, Lee et al, in our laboratory, reported that PDC activity and expression are increased in both renal proximal tubule cells and cortical homogenates from spontaneously hypertensive rats compared with normotensive Wistar-Kyoto rats ( Lee et al, 2014 ). This activation may be involved in the increase in the expression of sodium transporters and channels in nephron segments, including the renal proximal tubule ( Knepper and Brooks, 2001 ; Wang et al, 2009 ; Maxwell et al, 2020 ; Pitzer et al, 2020 ).…”
Section: Renal Dysfunction In Metabolic Syndromementioning
confidence: 99%
“…Recently, Lee et al, in our laboratory, reported that PDC activity and expression are increased in both renal proximal tubule cells and cortical homogenates from spontaneously hypertensive rats compared with normotensive Wistar-Kyoto rats ( Lee et al, 2014 ). This activation may be involved in the increase in the expression of sodium transporters and channels in nephron segments, including the renal proximal tubule ( Knepper and Brooks, 2001 ; Wang et al, 2009 ; Maxwell et al, 2020 ; Pitzer et al, 2020 ).…”
Section: Renal Dysfunction In Metabolic Syndromementioning
confidence: 99%
“…The hypothesis proposes that sodium can enter to APCs via epithelial sodium channel (ENaC) leading to intracellular formation of IsoLGs, in a process regulated by the Serum and Glucocorticoid Kinase-1 (SGK1) and by NADPH oxidase [23,32]. This mechanism is quite interesting because suggest a new role for ENaC inhibition in the therapy for AH [33].…”
Section: Sodium Effect On Immune Cells In Hypertensionmentioning
confidence: 99%
“…ENaC serves as one of several key final effectors of the renin-AngII-aldosterone system during regulation of blood pressure 8 . Abnormalities in ENaC function have been directly linked to several human diseases of blood pressure including the hypertensive state of Liddle’s syndrome and the hypotensive state of pseudohypoaldosteronism type I 5 , 6 , 9 .…”
Section: Introductionmentioning
confidence: 99%